Activation of Yes-Associated Protein in Low-Grade Meningiomas Is Regulated by Merlin, Cell Density, and Extracellular Matrix Stiffness. Issue 7 (July 2015) - Tanahashi, Kuniaki; Natsume, Atsushi; Ohka, Fumiharu; Motomura, Kazuya; Alim, Adiljan; Tanaka, Ichidai; Senga, Takeshi; Harada, Ichiro; Fukuyama, Ryuichi; Sumiyoshi, Naoyuki; Sekido, Yoshitaka; Wakabayashi, Toshihiko
Abstract : Abstract: The NF2 gene product Merlin is a protein containing ezrin, radixin, and moesin domains; it is a member of the 4.1 protein superfamily associated with the membrane cytoskeleton and also interacts with cell surface molecules. The mammalian Hippo cascade, a downstream signaling cascade of merlin, inactivates the Yes-associated protein (YAP). Yes-associated protein is activated by loss of the NF2 gene and functions as an oncogene in meningioma cells; however, the factors controlling YAP expression, phosphorylation, and subcellular localization in meningiomas have not been fully elucidated. Here, we demonstrate that merlin expression is heterogeneous in 1 NF2 gene-negative and 3 NF2 gene-positive World Health Organization grade I meningiomas. In the NF2 gene-positive meningiomas, regions with low levels of merlin (tumor rims) had greater numbers of cells with nuclear YAP versus regions with high merlin levels (tumor cores). Merlin expression and YAP phosphorylation were also affected by cell density in the IOMM-Lee and HKBMM human meningioma cell lines; nuclear localization of YAP was regulated by cell density and extracellular matrix (ECM) stiffness in IOMM-Lee cells. These results suggest that cell density and ECM stiffness may contribute to the heterogeneous loss of merlin and increased nuclear YAP expression in human meningiomas.